Relationship between agility tests and short sprints: reliability and smallest worthwhile difference in National Collegiate Athletic Association Division-I football players - Mann, J. B.; Ivey, P. A.; Mayhew, J. L.; Schumacher, R. M.; Brechue, W. F. (The Journal of Strength and Conditioning Research, 2016)
The Pro-Agility test (I-Test) and 3-cone drill (3-CD) are widely used in football to assess quickness in change of direction. Likewise, the 10-yard (yd) sprint, a test of sprint acceleration, is gaining popularity for testing physical competency in football players. Despite their frequent use, little information exists on the relationship between agility and sprint tests as well the reliability and degree of change necessary to indicate meaningful improvement resulting from training. The purpose of this study was to determine the reliability and smallest worthwhile difference (SWD) of the I-Test and 3-CD and the relationship of sprint acceleration to their performance. Division-I football players (n = 64, age = 20.5 ± 1.2 years, height = 185.2 ± 6.1 cm, body mass = 107.8 ± 20.7 kg) performed duplicate trials in each test during 2 separate weeks at the conclusion of a winter conditioning period. The better time of the 2 trials for each week was used for comparison. The 10-yd sprint was timed electronically, whereas the I-Test and 3-CD were hand timed by experienced testers. Each trial was performed on an indoor synthetic turf, with players wearing multicleated turf shoes. There was no significant difference (p > 0.06) between test weeks for the I-Test (4.53 ± 0.35 vs. 4.54 ± 0.31 seconds), 3-CD (7.45 ± 0.06 vs. 7.49 ± 0.06 seconds), or 10-yd sprint (1.85 ± 0.12 vs. 1.84 ± 0.12 seconds). The intraclass correlation coefficients (ICC) for 3-CD (ICC = 0.962) and 10-yd sprint (ICC = 0.974) were slightly higher than for the I-Test (ICC = 0.914). These values lead to acceptable levels of the coefficient of variation for each test (1.2, 1.2, and 1.9%, respectively). The SWD% indicated that a meaningful improvement due to training would require players to decrease their times by 6.6% for I-Test, 3.7% for 3-CD, and 3.8% for 10-yd sprint. Performance in agility and short sprint tests are highly related and reliable in college football players, providing quantifiable parameters for judging true change in performance as opposed to random measurement variation in college football players.